The Impact of the 2007-09 Credit Crunch on the Funding of Public Sector Infrastructure in the UK - Stephen J. Bailey; Darinka Asenova (Central European Public Administration Review)
The 2007-09 credit crunch has not only created problems for the UK’s public finances in meeting the costs of bailing out commercial banks and dealing with recession but also for providing better public services. This paper analyses the causes of the credit crunch, government policies to address it and its impact on the financing of new public sector infrastructure in the UK. It finds that provision of new public sector infrastructure and related services has been adversely affected by the impact of the credit crunch on Private Finance Initiatives (PFIs). Commercial banks are now generally only willing to lend to replace collapsed PFI bond financing if new PFI contracts reduce financial risks. By such means, PFIs can be expected to survive but within an increasingly diverse mixture of procurement methods.